A DESCRIPTIVE STUDY ON DIFFICULTIES IN WRITING RECOUNT TEXT FACED BY THE SECOND YEAR STUDENT AT SMA MUHAMMADIYAH 2 GEMOLONG IN IN 2010-2011 ACADEMIC YEAR - NUGROHO, IWAN CAHYO (2011)
The study is aimed at revealing the difficulties faced by the students and how does the teacher solves them in writing recount text in the second year students of SMA Muhammadiyah 2 Gemolong. This study is a qualitative study. The subject of the study refers to persons, or things to be studied and the object of the study is the difficulties in writing English recount text of second year students of SMA Muhammadiyah 2 Gemolong in 2010/2011 academic year. The data of this research are informations taken from three sources of the data that are event, document, and informant. In collecting the data, the writer used interview, observation, and document. The technique of the data analysis, the writer uses descriptive technique. The problems faced by the students in writing recount text are the students have difficulties to make a recount text based on its paragraph organization, the students have difficulties to express their ideas in long written language and the students have difficulties to use the correct grammar when they make a paragraph. The causes of problems faced by the students are the students are weak in determining the orientation, sequence of events and reorientation and also the use of past tense, the students are lack of idea and vocabulary mastery and the students are weak in using appropriate grammar to make recount text.